(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
Information abbaut the theatrical production staged in 2024 bye students from the Centro de Artes (CEART) at the Universidade do Estado de Santa Catarina (UDESC), directed by Paulo Balardim.